EGFR, p53, IDH-1 and MDM2 immunohistochemical analysis in glioblastoma: therapeutic and prognostic correlation - Richard Murdoch Montgomery; Luciano de Souza Queiroz; Fabio Rogerio (Arquivos de Neuro-Psiquiatria)
We studied 36 glioblastoma cases at HC-UNICAMP from 2008 to 2012 and classified the immunohistochemical distribution of the wild-type epidermal growth factor receptor (EGFR), mutated forms of p53 protein and isocitrate dehydrogenase-1 (IDH-1) and murine double protein 2 (MDM2). Immunostaining findings were correlated with clinical data and response to treatment (surgery, chemotherapy and radiotherapy). About 97% of the tumors were primary, most of them localized in the frontal lobe. Mean time free of clinical or symptomatic disease and free time of radiological disease were 7.56 and 7.14 months, respectively. We observed a significant positive correlation between expressions of p53 and MDM2, EGFR and MDM2. Clinical, radiological and overall survivals also showed a significant positive correlation. p53 staining and clinical survival showed a significant negative correlation. The current series provides clinical and histopathological data that contribute to knowledge on glioblastoma in Brazilians.